2023
DOI: 10.1186/s12880-023-00977-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of spleen stiffness measurement by 2D-shear wave elastography in evaluating the presence of high-risk varices: comparative analysis of idiopathic portal hypertension versus hepatitis B virus

Abstract: Background Noninvasive assessment of high-risk varices (HRV) in idiopathic portal hypertension (IPH) is rare. The purpose of this study was to investigate the performance of spleen stiffness (SS) for evaluating the presence of HRV in IPH patients as compared the measurements in patients with hepatitis B virus (HBV). Methods A retrospective single-center study was performed to evaluate the performance of SS for assessing HRV in IPH and HBV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Studies have shown that liver stiffness (LS) or spleen stiffness (SS) may be interrelated with GEV [8,9]. MRE has been introduced into clinical practice, and there have been several studies that have investigated the specific relationships between LS or SS and the presence of GEV [10,11]. Considering that the results and quality have considerable variability across different published studies, the diagnostic value and feasibility of MRE in detecting GEV remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that liver stiffness (LS) or spleen stiffness (SS) may be interrelated with GEV [8,9]. MRE has been introduced into clinical practice, and there have been several studies that have investigated the specific relationships between LS or SS and the presence of GEV [10,11]. Considering that the results and quality have considerable variability across different published studies, the diagnostic value and feasibility of MRE in detecting GEV remain elusive.…”
Section: Introductionmentioning
confidence: 99%